2008
DOI: 10.1080/10826080701204961
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Status and Alcohol Use Among Urban and Rural Residents in China

Abstract: The association between socioeconomic status (SES) and current regular alcohol use was examined separately for urban and rural residents of Hubei, China, using the third Chinese National Health Service Survey conducted in 2003. A probability sample of 15,609 respondents, ages 15 through 101 years, was selected from the study base. Alcohol use was a dichotomized variable (current regular users vs. others). Multivariate analyses incorporated four SES indicators: income, education, occupation, and house size. Inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
39
3
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 33 publications
8
39
3
1
Order By: Relevance
“…Fazel et al showed that low income and low level of education were associated with poor hypertension-related knowledge among adults in southern Iran [15]. Other studies also revealed the relationship between SES and hypertension-related behavior [16,17,18,19]. Smokers with lower education showed less willingness to quit and fewer quit attempts and reported a younger age in their smoking history [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fazel et al showed that low income and low level of education were associated with poor hypertension-related knowledge among adults in southern Iran [15]. Other studies also revealed the relationship between SES and hypertension-related behavior [16,17,18,19]. Smokers with lower education showed less willingness to quit and fewer quit attempts and reported a younger age in their smoking history [16].…”
Section: Introductionmentioning
confidence: 99%
“…A study revealed that sodium intake was associated with income levels among Japanese workers, and people with low incomes are less likely to use low-salt foods or follow salt restrictions [17]. Both urban and rural residents are less likely to partake in excessive drinking compared with high education and low incomes in China [18]. Even in patients with confirmed hypertension, lower education and incomes were also less likely to report involvement in blood pressure control [19].…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, the proportion of alcohol use among students with higher expenses in rural area was lower than that in urban area. Some literatures revealed that drinking is perceived as the most effective way of providing social support, and high-income urban people more like to social and increased social drinking occasions [23].…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14][15][16][17] La edad de mayor riesgo para el inicio del consumo de cannabis, así como de mayor riesgo para sus efectos, es la adolescencia y disminuye o cesa con cambios de vida como el inicio de actividades laborales en empleos de tiempo completo o el matrimonio. [18][19][20][21][22] El Trastorno por Déficit de Atención coexiste con el uso de sustancias entre el 34% y el 63% de los pacientes. Algunos estudios parentales han sugerido que cuando hay adecuada intimidad, autonomía y comportamientos de cuidado y protección existe un menor uso de sustancias; de igual manera se encuentra menor consumo con estilos autoritarios y de mayor supervisión parental.…”
Section: Mecanismos Neurobiológicos De La Cannabisunclassified